Gender and risk of depression in Saudi Arabia, a systematic review and meta-analysis - Osama A. Alibrahim; Nabilla Al-Sadat; Nagi A.M. Elawad (Journal of Public Health in Africa, 2010)
Depression is one of the leading causes of mortality and morbidity worldwide. In the year 2000 depression accounted for 4.4% of the global disability adjusted life years (DALYs). The Kingdom of Saudi Arabia (KSA) has a population of 28 million people and is one of the countries experiencing demographic transition in its population structure. Improvements in socioeconomic status have been shown to be associated with increased chronic diseases including chronic mental diseases like depression, but still there is no comprehensive review summarizing the various reports currently existing in the literature. Although individual studies within Saudi Arabia have reported prevalence rates and risks, the quality of such studies need to be subjected to rigorous assessment and their findings pooled to give combined weighted evidence that will provide basis for targeted intervention. Pooled risks have the advantage of adjusting inherent variations within sampled populations and therefore providing more reliable estimates even though there are concerns about possible magnification of smaller individual risks.